Lelang jabatan manajer puskesmas dan sistem monitoring berbasis komputer pada pekerja kesehatan: pengalaman reformasi administrasi di Jakarta - Eko Sriyanto; Mubasysyir Hasanbasri; Dwi Handono Sulistyo (Berita Kedokteran Masyarakat (BKM), 2018)
Performance monitoring of primary health centers chief internal contracting system in JakartaPurpose: This study aimed to describe internet-based electronic monitoring control mechanisms and problems that occur in policy implementation at the regional public service agency in Jakarta.Methods: A qualitative research with exploratory technique was conducted using semi-structured interviews, observation and document research. The research subjects were 12 people. The informants were chosen by purposive sampling. Data analysis used content analysis methods.Results: Results showed that attendance and performance of staff recorded in the system helped in managerial duties, the items of work have been standardized on the application of e-kinerja together with the points for incentives. While the number of human resources were less, omissions in time limit entry performance which resulted in non-payment of incentives served to encourage officers to report the activities in proper time. There were problems with the community in the form of false complaints of moral hazard but there is no filter mechanism against the false complaints.Conclusion: The results showed it difficult for health centers to prevent the complaints of moral hazard in the presence of a multi-layered monitoring system both internally and externally.